PENGARUH LA NINA TERHADAP CURAH HUJAN DI PROVINSI SUMATERA UTARA - Alfonsius C. P. Siregar; Nikita Pusparini; Theresia G. Simbolon; Siska C. Rajagukguk; Siti Chodijah; Joko Y. Ariantono; Carles A. Tari; Immanuel Jhonson Arizona Saragih (Republic of Indonesia Defense University, 2021)
El Nino and La Nina are global weather phenomena that occur in the equatorial Pacific Ocean and are generally associated with world climate anomalies. This study was conducted to determine the effect of the La Nina phenomenon on variations in rainfall in North Sumatra Province. The data used is 10 daily rainfall data (dasarian) for the period 1995 until 2020, the rainfall measurements data from the 39 rain observation sites spread across the North Sumatra region compiled by the Deli Serdang Climatology Station. Simple statistical methods were used to calculate rainfall intensity fluctuations, also the advance and retreat of the onset season during La Nina. The results showed that in general, the La Nina phenomenon had little effect on rainfall, rainy days, or the advance and retreat of the onset season in North Sumatra Province.